Definition and evaluation of plantar mechanical comfort for the support of footwear design. Issue 2 (3rd March 2016) - Papagiannis, Panagiotis; Koutkalaki, Zoi; Azariadis, Philip; Papanikos, Paraskevas
Abstract: Footwear is one of the most widely and intensively used human centric products. Evaluating and optimizing footwear performance is of outmost importance for human comfort. This paper presents a definition of foot plantar mechanical comfort along with a detailed approach for evaluating it through finite element analysis. An extensive review of biomechanical and shoe mechanical aspects related to human comfort is presented providing ample justification for the selection of the comfort characteristics which are addressed in this paper. A foot biomodel has been developed which is combined with solid shoe structures in order to evaluate plantar pressures distribution and shock absorption. In addition, bending and torsional behavior of shoe structures is also taken into account and, therefore, appropriate finite element models have been developed and tested. All experiments are analytically presented and discussed, while the related results illustrate the potential of the proposed approach to support footwear design optimization under an integrated biomechanics-enabled framework. GRAPHICAL ABSTRACT: